Adsorption Mechanism of Ciprofloxacin from Water by Synthesized Birnessite. (22nd March 2015) - Xing, Xuebing; Feng, Jingwen; Lv, Guocheng; Song, Kenan; Mei, Lefu; Liao, Libing; Wang, Xiaoyu; Xu, Ben
Abstract : The efficiency of ciprofloxacin (CIP) adsorption on synthesized birnessite was systematically studied under varying physicochemical conditions, such as solution pH, contact time, initial CIP concentration, and different average oxidation states (AOS) of Mn in birnessite. X-ray diffraction (XRD), Fourier transform infrared (FTIR), and molecular simulations were employed to investigate the adsorption mechanism of CIP on birnessite. Experimental results showed that surface adsorption instead of cation exchange was responsible for the uptake of CIP on birnessite. The quantum mechanics simulation showed that the final energy of the interaction between CIP and birnessite was smaller under the condition when the AOS of Mn was lower, in comparison to the case when the AOS of Mn was high. The highest CIP adsorption occurred under a weak alkaline condition.